Infant circulating MicroRNAs as biomarkers of effect in fetal alcohol spectrum disorders - Amanda H. Mahnke; Georgios D. Sideridis; Nihal A. Salem; Alexander M. Tseng; R. Colin Carter; Neil C. Dodge; Aniruddha B. Rathod; Christopher D. Molteno; Ernesta M. Meintjes; Sandra W. Jacobson; Rajesh C. Miranda; Joseph L. Jacobson (Scientific Reports, 2021)
Abstract Prenatal alcohol exposure (PAE) can result in cognitive and behavioral disabilities and growth deficits. Because alcohol-related neurobehavioral deficits may occur in the absence of overt dysmorphic features or growth deficits, there is a need to identify biomarkers of PAE that can predict neurobehavioral impairment. In this study, we assessed infant plasma extracellular, circulating miRNAs ( ex miRNAs) obtained from a heavily exposed Cape Town cohort to determine whether these can be used to predict PAE-related growth restriction and cognitive impairment. PAE, controlling for smoking as a covariate, altered 27% of expressed ex miRNAs with clinically-relevant effect sizes (Cohen’s d ≥ 0.4). Moreover, at 2 weeks, PAE increased correlated expression of ex miRNAs across chromosomes, suggesting potential co-regulation. In confirmatory factor analysis, the variance in expression for PAE-altered ex miRNAs at 2 weeks and 6.5 months was best described by three-factor models. Pathway analysis found that factors at 2 weeks were associated with (F1) cell maturation, cell cycle inhibition, and somatic growth, (F2) cell survival, apoptosis, cardiac development, and metabolism, and (F3) cell proliferation, skeletal development, hematopoiesis, and inflammation, and at 6.5 months with (F1) neurodevelopment, neural crest/mesoderm-derivative development and growth, (F2) immune system and inflammation, and (F3) somatic growth and cardiovascular development. Factors F3 at 2 weeks and F2 at 6.5 months partially mediated PAE-induced growth deficits, and factor F3 at 2 weeks partially mediated effects of PAE on infant recognition memory at 6.5 months. These findings indicate that infant ex miRNAs can help identify infants who will exhibit PAE-related deficits in growth and cognition.